Kepuasan Konsumen G. B Hotel Syari'ah Pekanbaru Ditinjau Dari Kualitas Pelayanan - Camelia, Yuni Putri; rupat, herman (Eko dan Bisnis: Riau Economic and Business Review, 2024)
This study aims to determine the effect of service quality on customer satisfaction at G. B Hotel Syari'ah Pekanbaru. The population in this study were all consumers who stayed at G. B Hotel Syari'ah Pekanbaru until December 2022 totaling 6,323 consumers. A sample of 98 consumers was taken referring to the Slovin formula, data collection techniques in this study were observation and questionnaires. The method used was descriptive and quantitative methods. Based on the results of the study, a simple linear regression equation was obtained of Y = 16,669 + 0.548 X. The results of the hypothesis test obtained t count > t table (12,889 > 1.985), with a significant value of 0.000 < 0.05, which means that service quality has a significant effect on customer satisfaction at G. B Hotel Syari'ah Pekanbaru. The magnitude of the influence is 63.4% while the remaining 36.6% is determined by other variables not included in this research model, for example, promotion, price and brand image. To improve service quality, it is recommended that management provide training to employees on service quality to further enhance it and meet customer expectations.